PENGARUH KONSENTRASI HYDROSOL DALAM MENGATASI SWABAKAR BATUBARA PADA STOCKPILE PT. BHUMI RANTAU ENERGI - Muhammad Nasrudin; Hesty Heryani; Syarifuddin Kadir; Ruslan Ruslan (EnviroScienteae, 2023)
Storing coal for a long duration of time in the stockpile can cause the company to lose money because the possibility of self-ignition is greater. Spraying treatment using hydrosol will wet the coal evenly so that it will coat the coal and can prevent self-ignition. This study was made to analyze changes in coal temperature due to the use of Hydrosol and determine the best Hydrosol concentration to prevent coal self-heating. The operational design of the research was by separating coal products. Then, four concentrations of Hydrosol were made to be applied to coal product by spraying. After spraying each coal product, data  were collected by measuring the temperature every day. The data from the research results showed the temperature increase for each coal product for 20 days of stacking so that it illustrated the effect of each Hydrosol concentration made and get the best concentration for application in the company's coal production pr˚Cess. The use of Hydrosol with four concentrations (0.0%; 0.5%, 1.O%; and 1.5%) with a treatment duration of 20 affected the temperature of the coal pile with a range of 32.4˚C to 55.3˚C where the initial critical temperature for self-heating was 50.7˚C. For this reason, coal with temperatures above 50˚C must be given treatment again such as compaction and spraying The best Hydrosol concentration to prevent self-heating during 20 days of stacking; as l.5o% Hydrosol concentration, which was a mixture of 98.5 liters of water with 1.5 liters of Hydrosol for every 10 tons of coal, which produced the lowest final temperature of all coal stacks, namely 41.3˚C.